Temperature conditions in the Argentine chub mackerel (Scomber japonicus) fishing ground: Implications for fishery management - Perrotta, Ricardo Geronimo (2001)
We describe the seasonal migrations of Argentine chub mackerel (Scomber japonicus) into the fishing ground in relation to sea surface temperature conditions and analyse the temperature evolution during the fishing season on the basis of 1955-97 time-series. The upper temperature limit for the presence of schools was around 19°C. At higher values, most schools leave coastal waters (< 50 m) for the shelf. An inverse relationship was observed between catches per unit of effort (CPUE) of the inshore fishery and sea surface temperature. The highest standardized CPUE values corresponded to temperatures lower than 19°C. Above this temperature, the probability of obtaining a standardized CPUE higher than 1 was extremely low, and the standard deviations were minimal. The economic benefit from catches was also analysed through the different months of the fishing season. It was found that the mean benefit corresponding to temperatures lower than 19°C exceeded approximately 15 times that obtained at higher temperatures. A simple fishing strategy was proposed to the commercial fleet in order to improve the economic benefit of the catches. The migratory pattern followed by mackerel during the spawning period was also analysed in relationship to other environmental factors like food availability. Zooplankton composition, size structure and abundance in coastal and shelf waters are described, and their implications for feeding ecology of larvae and adults of the species are discussed.